Assessment of procurement process of carriage rehabilitation project at Saidpur workshop implemented by Bangladesh railway based on Key Performance Indicators (KPI - Rahman , Md. Habibur (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.